2022
DOI: 10.1002/nano.202200188
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 and omicron variant detection with a high selectivity, sensitivity, and low‐cost silicon bio‐nanosensor

Abstract: The recent SARS-CoV-2 pandemic has highlighted the urgent need for novel point-of-care devices to be promptly used for a rapid and reliable large screening analysis of several biomarkers like genetic sequences and antibodies. Currently, one of the main limitations of rapid tests is the high percentage of false negatives in the presence of variants and, in particular for the Omicron one. We demonstrate in this work the detection of SARS-CoV-2 and the Omicron variant with a cost-effective silicon nanosensor enab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Based on these variabilities, the corresponding sensing performances are wide and they range between some thousands of cps to few cps per reaction (10 5 -2 cps/reaction). Respect to the real clinical samples, there are two examples [65,87] that prove the possibility for real use in qualitative test (yes/no answers), while only one study [83] demonstrated a quantitative detection using extracted real SARS-Cov-2 samples with a LoD of 4 cps/reaction, overcoming the PCR LoD that corresponds to ≈10 cps/reaction. Based on the above considerations, it is evident that, although these technology are very promising, however further extensive clinical validations are necessary to be used in commercial assays.…”
Section: Pcr-free Sensors Based On the Rna Sequence Direct Modificati...mentioning
confidence: 99%
See 4 more Smart Citations
“…Based on these variabilities, the corresponding sensing performances are wide and they range between some thousands of cps to few cps per reaction (10 5 -2 cps/reaction). Respect to the real clinical samples, there are two examples [65,87] that prove the possibility for real use in qualitative test (yes/no answers), while only one study [83] demonstrated a quantitative detection using extracted real SARS-Cov-2 samples with a LoD of 4 cps/reaction, overcoming the PCR LoD that corresponds to ≈10 cps/reaction. Based on the above considerations, it is evident that, although these technology are very promising, however further extensive clinical validations are necessary to be used in commercial assays.…”
Section: Pcr-free Sensors Based On the Rna Sequence Direct Modificati...mentioning
confidence: 99%
“…Reproduced with permission under the terms of the CC BY license. [ 83 ] Copyright 2023, the Authors. Published by Wiley‐VCH GmbH.…”
Section: Pcr‐free Strategies For Sars‐cov‐2 Poc Detectionmentioning
confidence: 99%
See 3 more Smart Citations